PREDIKSI DAMPAK PERUBAHAN TATAGUNA LAHAN TERHADAP DEBIT LIMPASAN, STUDI KASUS: GEREJA RANCASARI - Wijaya, Obaja Triputera; Yudianto, Doddi; Fitriana, Finna; Sanjaya, Stephen (JURNAL SUMBER DAYA AIR, 2024)
Flooding is one of the most frequent natural disasters in Indonesia. Based on data, as of 2024, there have been 137 cases of flooding incidents. One of the causes of flooding, particularly in urban areas, is due to land use change. This study examines the impact of land use changes on runoff discharge in a Church area in the Bandung City. Additionally, this study investigates the effect of the development of this area on flood water levels in the Riung channel, which serves as an outlet channel. In this study, modeling is conducted using the SWMM model. The study utilizes data from the BMKG Bandung and GPM satellite rainfall data from 2001 to 2022 for rainfall analysis. The results indicate that in the study area, the duration of extreme rainfall producing maximum discharge is rainfall lasting for 7 hours. As a result of the church development, runoff discharge increases by 26.3 – 34.4% across various return periods. For time to peak, there is no significant change in conditions before and after the area is developed. This is due to area is relatively small, resulting in a relatively shorter concentration time. Based on the hydraulic analysis, the Riung channel is still able to accommodate additional runoff generated due to development, leaving a freeboard height of 4.5 cm for a 10-year return period. However, based on observations, special attention is needed regarding the issue of sedimentation and trash, which often causes backflow in several segments of the trenches.Keywords:runoff, land use change, urban drainage, SWMM, Bandung